Hölderlin: ein romantischer oder ein romantisierter Dichter? Fragment, Umnachtung, ‘obscuritas’, Revolution - Elena Polledri (Studia theodisca)
This article aims to show how and why a poet who is not classified as a Romantic in literary historical terms, but as one who stands between Classicism and Romanticism and who himself spoke out against Romanticism, was romanticised or became a Romantic in the course of the 20th century. After an introduction to the state of research on Hölderlin and Romanticism and the poet’s relationships with the Romantics of his time, the essay concentrates on Hölderlin’s reception as a Romantic and identifies the main elements that led to the Romantic mythicisation of the poet as: the fragmentary nature of his work, the poet’s identification with his tragic, insane character, obscuritas and the revolution. The second part of the article emphasises Hölderlin’s constant search for ‘measure’, an ever-present feature of his work, with the aim of showing that the figure of the tragic Romantic poet, which his reception has emphasised by focusing on Romantic potential in his writing, is to be distinguished from the poet Hölderlin and his work.